2012
DOI: 10.4172/2155-952x.1000124
|View full text |Cite
|
Sign up to set email alerts
|

A Single Bio-based Catalyst for Bio-fuel and Bio-diesel

Abstract: Current homogeneous catalysts used for commercial biodiesel synthesis are toxic and flammable. For Feedstock, their reaction requires refined oil which is a human food and expensive. In addition, due to contamination, the main byproduct of their reaction, glycerol is not usable for sale as a high value product and is land filled or burned as waste. Furthermore, the use of these catalysts in conversion of low cost feed-stocks such as waste oil and greases is not economical because their reactions produce soaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Hence, this explains the poor catalytic performances at 600°C. Moreover, high catalyst loading effect negatively on the yield due to ether formation generated from the excess of acid [18]. Besides that, emulsifications occurred when excess of catalyst loading is applied and in the long run affects the separation between FAME and by product.…”
Section: Effect Of Catalytic Activity On Fame Yieldmentioning
confidence: 99%
“…Hence, this explains the poor catalytic performances at 600°C. Moreover, high catalyst loading effect negatively on the yield due to ether formation generated from the excess of acid [18]. Besides that, emulsifications occurred when excess of catalyst loading is applied and in the long run affects the separation between FAME and by product.…”
Section: Effect Of Catalytic Activity On Fame Yieldmentioning
confidence: 99%
“…Due to the abundance of cellulosic biomass in the nature they are usually used to produce activated carbon as the catalytic active site in these catalysts are chemically bound, as a result both the biodiesel and glycerol by-product will be free of catalysts contaminants (Emrani and Shahbazi 2012 ). For biomass derived CBSC, the body is often amorphous and owns aromatic structure.…”
Section: Biomass Derived Activated Sulfonated Catalystmentioning
confidence: 99%
“…The oxidation of carbon is not the only way of introducing grafted acid groups onto their surface. Protonated surface functionalization can also be achieved by the phosphorylation of active carbon and other carbonaceous materials in the case of their heat treatment with phosphoric acid [7][8][9][10] or by the sulfonation with concentrated sulfuric acid (sulphonated carbon) [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has also been shown that the sulfonation of incompletely carbonized cellulose, starch, glucose and some polymers makes it possible to get hard carbon-based insoluble solid acids, which can potentially be uses as a replacement for the homogenous sulphuric acid catalyst [11][12][13][14][15][16][17]. Meanwhile, mainly for historical reasons, oxidized, sulphonated, and phosphorylated carbon were studied mainly as cation exchangers with high selectivity towards multiply charged cations [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation